Penilaian Kinerja dan Peningkatan Kinerja Mengggunakan Metode Balanced Scorecard (BSC) dan Quality Functions Deployment (QFD) Di PT. Laksana Anda Jaya - Mamonto, Muhammad Eko; Suparjo, Suparjo (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
PT. Laksana Anda Jaya is a company that operates in the field of providing products and services. Based on the results of observations made by researchers, that the company experienced a decline in revenue, the results in this study using the Balanced Scorecard obtained 4 perspectives, namely. From a financial perspective, looking at Retrun on Capital Employed (ROCE), it is known that during 2021 to 2022 there has been an increase with a target value of 19%, while Retrun On Investment is known to have decreased by 3% during 2021 to 2022, while for operating costs the target achieved has increased by value of 149% in 2021 to 2022, customer perspective as a result of distributing questionnaires which resulted in a customer satisfaction level of 15% with products/services, internal business perspective with innovation processes and after-sales services provided by the company PT. Laksana Anda Jaya at 3.53% and after sales with a target value of 2.95% and operations processes with a target value of 3.57, a learning and growth perspective provides a target value of 20% and employee retention with a target value of 100%. Meanwhile, for the Quality Function Deployment approach, there are several suggestions for improvements that PT needs to improve. Anda Jaya's implementation in the results of these improvement proposals is that there are 6 proposals that need to be prioritized, namely, creating a marketing division (Marketing), building intense relationships with customers, building working relationships with customers, improving performance and providing guarantees, providing a suggestion box and a means for customer complaints and improve the quality of raw materials.